Effects of Combined Plyometric and Short Sprints Training on Athletic Performance of Male U19 Soccer Players - Aloui, Ghaith; Souhail, Hermassi; Hayes, Lawrence D.; Bouhafs, El Ghali; Chelly, Mohamed Souhaiel; Schwesig, René (Frontiers in Psychology, 2021)
This project investigated adding 8 weeks of bi-weekly plyometric and short sprints training into standard training in elite youth soccer players. An experimental group (EG, n = 18, age: 17.6 ± 0.6 years, body mass: 67.6 ± 5.8 kg, height: 1.75 ± 0.06 m, body fat: 11.5 ± 1.6%), and control group (CG, n = 18, age: 17.5 ± 0.6 years, body mass: 68.8 ± 3.6 kg, height: 1.77 ± 0.04 m, body fat: 11.7 ± 1.2%), participated. Pre- and post-intervention measures were squat-jump (SJ), countermovement-jump (CMJ), standing long jump (SLJ), 5 m and 20 m sprint, change-of-direction ability (4 x 5 m sprint test [S 4 x 5 m] and sprint 9–3–6–3–9 m with backward and forward running [SBF]), repeated change of direction (RCOD), and static balance (stork balance test). For all parameters, significant (p<0.001, p2>0.10) time and interaction (group x time) effects were observed. For three parameters (SBF, RCOD fastest time, SLJ) no significant group effects were observed. The EG consistently showed a significant higher performance level than the CG and a higher amount of effect sizes d (EG: drange: 1.27-2.61; CG: drange: 0.13-0.79) as an indicator for development of performance between pre- and post-intervention measures. Adding bi-weekly plyometric and short sprint training to standard training improves athletic performance of young soccer players. Such plyometric and short sprint training conditioning can be highly recommended as part of the annual short training program for male elite U19 soccer players.